NanI and NanJ Sialidases of Clostridium perfringens Are Not Essential for Virulence - Chiarezza, Martina; Lyras, Dena; Pidot, Sacha J; Flores-Díaz, Marietta; Awad, Milena M; Kennedy, Catherine L; Cordner, Leanne M; Phumoonna, Tongted; Poon, Rachael; Hughes, Meredith L; Emmins, John J; Alape-Girón, Alberto; et al. (Infection and Immunity, 2009)
The essential toxin in Clostridium perfringens-mediated gas gangrene or clostridial myonecrosis is alpha-toxin, although other toxins and extracellular enzymes may also be involved. In many bacterial pathogens extracellular sialidases are important virulence factors, and it has been suggested that sialidases may play a role in gas gangrene. C. perfringens strains have combinations of three different sialidase genes, two of which, nanI and nanJ, encode secreted sialidases. The nanI and nanJ genes were insertionally inactivated by homologous recombination in derivatives of sequenced strain 13 and were shown to encode two functional secreted sialidases, NanI and NanJ. Analysis of these derivatives showed that NanI was the major sialidase in this organism. Mutation of nanI resulted in loss of most of the secreted sialidase activity, and the residual activity was eliminated by subsequent mutation of the nanJ gene. Only a slight reduction in the total sialidase activity was observed in a nanJ mutant. Cytotoxicity assays using the B16 melanoma cell line showed that supernatants containing NanI or overexpressing NanJ enhanced alpha-toxin-mediated cytotoxicity. Finally, the ability of nanI, nanJ, and nanIJ mutants to cause disease was assessed in a mouse myonecrosis model. No attenuation of virulence was observed for any of these strains, providing evidence that neither the NanI sialidase nor the NanJ sialidase is essential for virulence.